Carbon Monoxide (Co) Level in Exhaled Breath of Smoker High School Students - Affriany Prasetyo, Raden Putri Annisya; Zakiah; Kaaffah, Silmy (Universitas Airlangga, 2024)
Background: Smoking behavior is one of the health behavior problems throughout the ages among young generations in Indonesia. Hence, smoking or tobacco use remains a global epidemic as it is devastating global health and economic costs. Aims: This study aims to find the relationship between smoking and CO Levels in exhaled breath among high school students and to describe the proportion of smoking and other behavior risk factors. Method: This is a cross-sectional study with 438 respondents from 5 high schools in Sawangan Primary Health Care working area who are available to participate in this study and to be tested by the smoke analyzer. Result: The result of this study shows that from 297 (67,8%) smokers, 56 (12,8%) students were daily smokers, 177 (40,4%) students were periodic smokers, and 64 (14,6%) students ever tried smoking even just once in a lifetime. This study also describes that the CO level in exhaled Breath was 2,64 ppm on average with a maximum level of 34 ppm. Using the Kruskal Wallis test, this study found a significant relationship between smoking behavior and CO level in exhaled breath. Besides that, the chi-square test in this study shows that there were different proportions between sex, type of smoke, having a smoker in a family member, and willingness to quit smoking with smoking behavior. Conclusion: it can be concluded that smoking behavior impacts the level of Carbon Monoxide inside the body and smoking behavior can be differentiated and impacted by multiple factors.